2023
DOI: 10.1186/s42358-023-00291-6
|View full text |Cite
|
Sign up to set email alerts
|

Blood levels of brain-derived neurotrophic factor (BDNF) in systemic lupus erythematous (SLE): a systematic review and meta-analysis

Abstract: Objectives BDNF has been implicated in the pathophysiology of systemic lupus erythematosus (SLE), especially its neuropsychiatric symptoms. The purpose of this study was to investigate the profile of blood BDNF levels in patients with SLE. Methods We searched PubMed, EMBASE, and the Cochrane Library for papers that compared BDNF levels in SLE patients and healthy controls (HCs). The Newcastle–Ottawa scale was used to assess the quality of the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Therefore, p75 NTR signaling may exert potential effects on mitochondrial metabolism in B cells to participate in the regulation of SLE pathogenesis ( Figure 5 ). Similar to the upregulation of proBDNF, BDNF levels in B cells and serum increased in patients with SLE compared with healthy controls ( 117 , 118 ). However, the level of serum BDNF and the number of BDNF + B cells were independent of the SLEDAI score ( 117 ).…”
Section: Probdnf and Its Receptors In Slementioning
confidence: 76%
“…Therefore, p75 NTR signaling may exert potential effects on mitochondrial metabolism in B cells to participate in the regulation of SLE pathogenesis ( Figure 5 ). Similar to the upregulation of proBDNF, BDNF levels in B cells and serum increased in patients with SLE compared with healthy controls ( 117 , 118 ). However, the level of serum BDNF and the number of BDNF + B cells were independent of the SLEDAI score ( 117 ).…”
Section: Probdnf and Its Receptors In Slementioning
confidence: 76%
“…The altered expression of enriched genes including CX3CR1 [599], S100A12 [600], PF4 [601], MPO (myeloperoxidase) [602], RXFP1 [603], S100A8 [604], VEGFD (vascular endothelial growth factor D) [605], CXCL11 [606], IL1A [607], BPI (bactericidal permeability increasing protein) [608], SLC6A4 [609], CXCL10 [610], FCGR3B [611], S100A9 [612], IL1B [613], CXCR2 [614], CTNND2 [615], CD36 [616], PCSK9 [617], FGF2 [618], SHH (sonic hedgehog signaling molecule) [619], KL (klotho) [620], BMPR2 [621], TLR8 [622], GATA3 [623], CCR2 [624], TLR7 [625], CAV1 [626], TFPI (tissue factor pathway inhibitor) [627], and SPAG17 [628] have been proposed as novel biomarkers for systemic sclerosis. A previous study found that enriched genes including CX3CR1 [629], S100A12 [630], MPO (myeloperoxidase) [631], CD5L [632], F11 [633], S100A8 [634], BPI (bactericidal permeability increasing protein) [635], AQP4 [636], MME (membrane metalloendopeptidase) [637], BDNF (brain derived neurotrophic factor) [638], CXCL10 [639], RNASE2…”
Section: Discussionmentioning
confidence: 99%
“…The altered expression of CX3CR1 [599], S100A12 [600], PF4 [601], MPO (myeloperoxidase) [602], RXFP1 [603], S100A8 [604], VEGFD (vascular endothelial growth factor D) [605], CXCL11 [606], IL1A [607], BPI (bactericidal permeability increasing protein) [608], SLC6A4 [609], CXCL10 [610], FCGR3B [611], S100A9 [612], IL1B [613], CXCR2 [614], CTNND2 [615], CD36 [616], PCSK9 [617], FGF2 [618], SHH (sonic hedgehog signaling molecule) [619], KL (klotho) [620], BMPR2 [621], TLR8 [622], GATA3 [623], CCR2 [624], TLR7 [625], CAV1 [626], TFPI (tissue factor pathway inhibitor) [627] and SPAG17 [628] have been identified in systemic sclerosis. A previous study found that CX3CR1 [629], S100A12 [630], MPO (myeloperoxidase) [631], CD5L [632], F11 [633], S100A8 [634], BPI (bactericidal permeability increasing protein) [635], AQP4 [636], MME (membrane metalloendopeptidase) [637], BDNF (brain derived neurotrophic factor) [638], CXCL10 [639], RNASE2 [640], FCGR3B [641], S100A9 [642], GPIHBP1 [643], AFF3 [644], APOH (apolipoprotein H) [645], FCN3 [646], PCSK9 [308], LILRA2 [647], APOA1 [648], LRRK2 [649], CD244 [650], TLR3 [651], TLR8 [652], GATA3 [653], CCR2 [654], IFIT3 [655], NEK7 [656], TLR7 [657], CAV1 [658], CR1 [659], TFPI (tissue factor pathway inhibitor) [660], GPER1 [661], SIGLEC14 [662], FOXJ1 [663], GABRP (gamma-aminobutyric acid type A receptor subunit pi) [664] and TSGA10 [665] are positively correlated with the severity of systemic lupus erythematosus, suggesting its potential as a biomarker ...…”
Section: Discussionmentioning
confidence: 99%